Combined Statistical Analyses of Forensic Evidence in Sexual Assault: A Case Report and Brief Review of the Literature. Issue 5 (2nd July 2020) - Tozzo, Pamela; Gabbin, Andrea; Politi, Caterina; Da Pian, Marta; Caenazzo, Luciana; Causin, Valerio
Abstract: DNA analysis has been widely used in the forensic field in order to contribute to identifying the perpetrator of a crime. Forensic investigation in sexual assaults usually focuses on locating and identifying biological fluids, followed by DNA analysis. The identification of certain compounds present in condoms can be useful to reconstruct the occurred event, especially in cases of sexual assaults where the DNA analysis did not show the presence of a male profile and where RNA analysis did not show the presence of sperm markers. Herein we describe the case of a woman reporting to be victim of sexual assault, who was not able to provide accurate information concerning the dynamics of the event; she remembered only forced penile–vaginal penetration by a single perpetrator. We performed short tandem repeat (STR) analyses and mRNA typing for forensic genetics testing on vaginal and rectal swabs collected on the victim, and Fourier‐transform infrared spectroscopy (FTIR) followed by chromatographic analyses for the detection of condom compounds on the same swabs. The STR analysis showed only the victim's genetic profile, and RNA analysis showed only the presence of vaginal and skin markers. In this situation, the identification of condom compounds residues on vaginal swabs became important as it complemented other collected evidences allowing the Court to reconstruct the events. A proposal of likelihood ratio (LR) calculation for the assessment of the weight of evidence in this case is described.